Firearm Storage in Gun-Owning Households with Children: Results of a 2015 National Survey - Azrael, Deborah (J Urban Health, 2018)
Data from a nationally representative probability-based online survey sample of US adults conducted in 2015 (n = 3949, response rate 55%) were used to assess self-reported gun storage practices among gun owners with children. The presence of firearms and children in the home, along with other household and individual level characteristics, was ascertained from all respondents. Questions pertaining to household firearms (how guns are stored, number, type, etc.) were asked only of those respondents who reported that they personally owned a gun. We found that approximately one in three US households contains at least one firearm, regardless of whether children lived in the home (0.34 [0.29–0.39]) or not (0.35 [0.32–0.38]). Among gun-owning households with children, approximately two in ten gun owners store at least one gun in the least safe manner, i.e., loaded and unlocked (0.21 [0.17–0.26]); three in ten store all guns in the safest manner, i.e., unloaded and locked (0.29, [0.24–0.34]; and the remaining half (0.50 [0.45–0.55]) store firearms in some other way. Although firearm storage practices do not appear to vary across some demographic characteristics, including age, sex, and race, gun owners are more likely to store at least one gun loaded and unlocked if they are female (0.31 [0.23–0.41]) vs. male (0.17 [0.13–0.22]); own at least one handgun (0.27 [0.22–0.32] vs. no handguns (0.05 [0.02–0.15]); or own firearms for protection (0.29 [0.24–0.35]) vs. do not own for protection (0.03 [0.01–0.08]). Approximately 7% of US children (4.6 million) live in homes in which at least one firearm is stored loaded and unlocked, an estimate that is more than twice as high as estimates reported in 2002, the last time a nationally representative survey assessed this outcome. To the extent that the high prevalence of children exposed to unsafe storage that we observe reflects a secular change in public opinion towards the belief that having a gun in the home makes the home safer, rather than less safe, interventions that aim to make homes safer for children should address this misconception. Guidance alone, such as that offered by the American Academy of Pediatrics, has fallen short. Our findings underscore the need for more active and creative efforts to reduce children’s exposure to unsafely stored firearms.